Validity of Local Wisdom-Based Insets Learning Model to Improve Critical Thinking Skills of Senior High School Students - Fincensius Oetpah; Erman Erman; Yuni Sri Rahayu (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This study aims to produce a valid learning tool for the local wisdom-based insets model to improve the critical thinking skills of high school students. Method: This research uses the Instructional Design Model (IDM) 1) needs analysis, 2) design and development of prototypes, 3) validation of socio-scientific issues, and 4) testing of socio-scientific issues prototypes. socio-scientific issues validation, 4) socio-scientific issues prototype testing, 5) socio-scientific issues evaluation, 6) socio-scientific issues revision. Validity was measured based on validation results from three expert lecturers. Data analysis was done descriptively and quantitatively. Results: The overall average test results of content validity with a very valid category, the overall average of construct validity with a very valid category, and the overall average validity of learning devices with a very valid category. The results showed that the insets model learning device based on local wisdom is valid for improving the critical thinking skills of high school students. Novelty: Students' critical thinking skills can be trained by integrating local wisdom-based insets learning model for 21st-century education.